Evaluation of some respiratory functions of Kyrgyz national team athletes before 2016 Summer Olympic Games - Demirhan, B.; Abdurahmanova, D.; Canuzakov, K.; Geri, S. (International Journal of Human Sciences, 2018)
In this study, some respiratory functions of athletes from four different sport branches who constitute Kyrgyzstan National Team have been examined. To research, 9 Greco-Roman style wrestlers (24±4,5years), 10 freestyle wrestlers (22,10±3,21 years), 8 judoists (23,6±1,89 years), 8 male athletes (22,29±2.87 years) and 3 female athletes (21.67±2.08 years) totally 35 male and 3 female national athletes have been included. Forced vital capacities (FVC), forced ventilation volumes (FEV1) and peak expiratory flow (PEF) which connected the respiratory levels of the athletes have been measured in preparation stage before 2016 Summer Olympic Games. By being performed istatistical evaluation by SPSS 21.0, it was used the computer package program. "One Way ANOVA" test an identifying the differences between the groups and the differences at (P<0,05) level have been accepted as significant. FVC values taken from Judoists were similar to those of male athletes (p>0,05) and significantly higher than other branches (p<0,05). FVC levels of wrestling and athletic athletes reflected similar results (p>0,05). When PEF levels examined, the results of judo and male athletes have been found statistically similar (p>0,05). PEF scores of Greco-Roman wrestling, freestyle wrestling and female athletes have not been found statistically different (p>0,05). FEV1 results of the judoists have been found similar to those of the Greco-Roman style wrestlers (p>0,05) while these results have been found significantly higher than the results of freestyle wrestling and athletic athletes (p<0,05). As a result, Judo athletes' FVC, PEF and FEV1 levels have been found better than other branches involved in the study.